Why Swedes Don’t Wear Face Masks During the Pandemic—A Consequence of Blindly Trusting the Government (Journal of International Crisis and Risk Communication Research, 2021)
Government trust is generally helpful for societies, especially in crisis situations, such as during the COVID-19 pandemic, because governments rely on citizens to follow directives. Worldwide, with supporting evidence accumulating, a key directive has been to wear face masks. However, in Sweden, the government has questioned their usefulness. On other behavioral recommendations, such as handwashing, the government has taken a conventional path. We rely on this non-recommendation of face masks to examine the causal impact of government trust on behavior. Based on a large Swedish survey fielded during the pandemic, we find that higher government trust reduces the likelihood of wearing face masks. In contrast, higher trust increases the likelihood of handwashing. The findings qualify the conclusion about the beneficial consequences of trust.